OZONETHERAPY AND LEGISLATION Analysis for its regularization (Ozone Therapy Global Journal, 2012)
Ozonethe rapy is on the agenda and figures at test to its growing importance. Theozonetherapy is increasingly practiced in different parts of the world. The existence ofmore than 40 national and international associations of ozonetherapy and more than26 000 ozonetherapists confirm it. However, while ozone was discovered in 1785 byDutch physicist Martin van Marum (1750-1837) and had been synthesized in May 1840by the German chemist Christian Friedrich Schönbein (1799-1868), history has shownthat it has been difficult to have a significant presence in the world's medical agendas.Only Russia, Cuba, Spain and Italy have provisions from the authorities that specifythe criteria to be met so that they can practice. These provisions are analyzed in thisstudy, to rule in favor of working for the regularization of ozonetherapy, with referenceto the measu res taken by the se countries. Specific points are proposed and amethodology that should be taken into account when developing a strategy that canlead to the regularization of ozonetherapy in countries where it is still widely practiced